Factors Influencing the Efficiency of Public Hospitals in Saudi Arabia: A Qualitative Study Exploring Stakeholders' Perspectives and Suggestions for Improvement - Alatawi, Ahmed D.; Niessen, Louis W.; Bhardwaj, Minakshi; Alhassan, Yussif; Khan, Jahangir A. M. (Frontiers in Public Health, 2022)
Objective Despite an extensive literature on efficiency, qualitative evidence on the drivers of hospital efficiency is scant. This study examined the factors that influence the efficiencies of health service provision in public hospitals in the Kingdom of Saudi Arabia (KSA) and their potential remedies. Design We employed a qualitative design involving semi-structured interviews conducted between July and September 2019. Participants were purposively selected and included policymakers and hospital managers drawn from districts, regional and national levels. Data were analysed in Nvivo 12 based on a thematic approach. Setting Key informants of Ministry of health in the KSA. Results Respondents identified a range of different factors across the community, facility and the wider health system that influence inefficiencies in public hospitals in KSA. Ineffective hospital management, lack of strategic planning and goals, weak administrative leadership, and absence of monitoring hospital performance was noted to have a profound impact on hospital efficiency. The conditions of healthcare staff in respect to both skills, authority and psychological factors were considered to influence the efficiency level. Further, lack of appropriate data for decision making due to the absence of an appropriate health informatics system was regarded as a factor of inefficiency. At the community level, respondents described inadequate information on the healthcare needs and expectations of patients and the wider community as significant barriers to the provision of efficient services. To improve hospital efficiencies, respondents recommended that service delivery decisions are informed by data on community health needs; capacity strengthening and effective supervision of hospital staff; and judicious resource allocation. Conclusion The study demonstrates that inefficiencies in health services remain a critical challenge in public hospitals in KSA. Extensive awareness-raising and training on efficient resource utilisation among key health systems stakeholders are imperative to improving hospital performance. More research is needed to strengthen knowledge on hospital efficiency in light of the limited data on the topic in KSA and the wider Gulf region.